Mapping Conceptual Understanding of Experts, Teachers, and Students through Conceptual Metaphor Theory - Gierus, Bogusia (Peer Beyond Graduate Research Conference, 2025)
This study investigates conceptual understanding of quantum physics across expertise levels using conceptual metaphor theory. Interviews and focus groups with experts, teachers, and students revealed distinct metaphorical patterns. Experts exhibited complex, interconnected metaphors, while novices displayed fragmented and limited mappings. These findings demonstrate the role of metaphor in making meaning of abstract scientific concepts and offer insights into the development of expertise in quantum physics. By understanding the role of conceptual metaphors in learning and reasoning, we can develop more effective pedagogical approaches that foster deeper understanding and critical thinking skills.